International Practice of Storing Human Cell Lines Intended for Clinical Use - O. A. Rachinskaya; A. A. Chaplenko; E. V. Melnikova; I. S. Semenova; Yu. V. Olefir (Биопрепараты: Профилактика, диагностика, лечение, 2018)
Currently, the Russian Federation does not have a well-established state-controlled market for cell banks (CB) containing cell material that is potentially applicable for clinical purposes. Cryopreservation of cells in cell bank (CB) is an important step in the production of a number of biomedical cell products and makes it possible to overcome difficulties faced by manufacturers during production and storage of large amounts of cell material. At present there are a large number of human cell lines in the world, which are stored in CB owned by commercial and public organisations in different countries. In addition, new cell lines are being banked every year. All this makes it difficult to find cell material suitable for production purposes or that could potentially be used as donor material in clinics. This study analysed the international practice of storing human cell lines for clinical use. The authors of the study systematised the existing CB worldwide and analysed regulatory documents governing the activities of these banks in different countries. The analysis revealed a trend towards formation of CB, often specialising in certain types of cells, as well as a trend towards creation of registries giving full information about cell lines including data on their scientific application. The increasing development and clinical use of cell therapy products in the Russian Federation and abroad will most likely lead to the increase in the number of CB and registry systems, as well as amounts of materials stored in them, including cell lines intended for clinical use.